Industrial Agglomeration and Economic Growth in Indonesia (Universitas Negeri Semarang, 2023)
This study aims to analyze the level of industrial agglomeration using balassa index and spatial analysis. In addition, this study also analyzes the effect of industrial agglomeration, investment, infrastructure, and inequality on economic growth. The data used in this study are secondary data. This study uses panel data regression with a fixed effect model approach, consisting of 34 provinces in Indonesia for the period 2015-2020. The results of this study indicate that industrial agglomeration occurs in 7 provinces in Indonesia (Kepulauan Riau, West Java, Central Java, DI Yogyakarta, East Java, Banten, and Bali) with an average balassa index value of 1.34 and included in low levels. Industrial agglomeration tends to occur on Java Island. The results of the regression analysis in this study indicate that industrial agglomeration, investment, and infrastructure have a positive effect on economic growth in Indonesia, while inequality has a negative effect on economic growth in Indonesia.